Simulasi Proses Picking Order dengan Metode Dedicated Storage Menggunakan Software Fleksim (Studi Kasus PT XYZ) - Amalia, Diana Nur; Fayaqun, Reza; Bisma, M Ardhya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT XYZ is a manufacturing company that produces food and drinks by providing quality products that are halal, high quality and safe for consumption by the public. In producing products, companies must provide several adequate facilities to support production activities, one of which is warehouse facilities. Currently, warehouses where finished food products are stored are stored randomly or placed in empty areas without paying attention to product entry and exit activities. This condition causes picking activities to take a long time and makes stock monitoring difficult. The aim of this research is to produce an appropriate goods storage design so that it can increase warehouse effectiveness. This research uses a special storage method. Where a special storage policy or method is permanently placed on each item. The number of product storage locations must meet the maximum storage space requirements and a simulation is carried out using FlexSim software. The research results show that designing goods storage using the dedicated storage method results in a reduction in the distance traveled for the collection process reaching 52%.